A Qualitative Study: Stigma Among People With Mental Disorders - Dhita Kurnia Sari; Mita Yani Nur Azizah; Reni Nurhidayah; Lingga Kusumawardani; Faizzaturohim (Universitas STRADA Indonesia, 2025)
Background: One of the problems in treating mental disorders is societal stigma. The stigma against people with mental disorders is in the form of negative views towards people with mental disorders. Purpose: The aim of this research is to determine the public stigma towards people with mental disorders in Nglebeng Village, Panggul District, Trenggalek District. Methods: This research design is qualitative with phenomenology approach. Informants were taken using a purposive sampling technique who met the inclusion and exclusion criteria with 4 informants. Data collection techniques through in-depth interviews and documentation with informants. Test the validity of the data where the researcher uses source triangulation. Data were analyzed using thematic analysis. Results: Based on the results of this research. Based on the results of this research, 3 major themes were found, namely: 1. Community knowledge of people with mental disorders, 2. Factors forming community stigma towards people with mental disorders, 3. Community attitudes and behavior towards people with mental disorders. Conclusion: Based on the research results, it can be concluded that the cause of the emergence of public stigma is the lack of information and public knowledge about what people with mental disorders.